Effectiveness of "Greening" the Professional Education Courses in Teacher Education Program in the National Network of Normal Schools - Rebecca Rosario O. Bercasio (Randwick International of Education and Linguistics Science Journal, 2022)
This study determined the effectiveness of the Professional Education lessons embedded with environmental concepts and principles using the materials from the Department of Environment and Natural Resources (DENR). It involved the 399 third Teacher Education students from the eight member institutions of the National Network of Normal Schools (3NS) during the first term of the academic year 2016-2017. Data gathering strategies were parallel pretest and posttest, focus group discussion, document analysis, and process documentation of the class project implementation. Data sources were the results of validated researcher-made Test on Environmental Concepts and Principles, focus group discussion, analysis of the curriculum guide, and the documentation of the students’ environmental project implementation. The t-test (4.443) between the pre-test mean of 14.50 and the post-test mean of 18.83 showed a significant increase in the test at 0.05 level of significance. The results show that the EE-enriched lessons in Professional Education courses were found effective in enhancing the level of environmental competence of the students based on the test results and supported by the students’ narratives and project implementation. The institutionalization of the integration of environmental education in the Professional Education courses in the Teacher Education curriculum is strongly recommended.